The Boundary of the Reduction of Citizens’ Right to Education in Major Public Emergencies - Xiner Ni (Studies in Law and Justice, 2023)
The boundary of the reduction of citizens’ right to education in major public emergencies is an important practical issue that adheres to the rule of law principle and the bottom line of social justice. Understanding the constitutional connotation of the right to education and judging whether the major public emergencies represented by the COVID-19 pandemic can provide a legitimate basis for its reduction is an important premise for the study of this issue. According to the relevant provisions of China’s Constitution and laws and the academic research on the connotation of the right to education, the right to education is the basic right of citizens, with the dual attributes of right and duty, freedom and social rights, equality and process. According to the theory of “minimum human rights” and “non-derogable rights”, major public emergencies can provide a certain justification for the reduction of the right to education, but this kind of reduction has a boundary. In constructing the boundary of the reduction of the right to education, the bottom line should be that the substance of the right to education should not be violated, the coordination and unity of the individual interests of educated citizens and the social public interests to curb the spread of the epidemic should be the key, and the principle of proportionality should be the guideline.